Effect of masked abrasive waterjet texturing on surface roughness using Taguchi method - Husin, Hafiz; Zaidi, Norman; Gebremariam, M. A.; Azhari, Azmir (Springer, Singapore, 2022)
High pressure waterjet technology has received a wider acceptance for various applications involving machining, cleaning, surface treatment and material cutting. Surface texturing is a popular method to improve the wear resistance of a surface. The present study applied a masked abrasive waterjet texturing pro-cess to produce a circular crater on a surface of stainless steel 304. The effect of machining parameters namely traverse rate, water pressure, standoff distance and number of passes on the roughness of the crater surface was analysed. Taguchi method of experimental design was employed by utilizing the L9 orthogonal array. The result shows that the water pressure is the most significant parameter in determining the roughness of the crater surface. Also, based on at the optimum parameters has shown an improvement of surface roughness as compared the initial optimal setting. This shows that the Taguchi method can be conveniently used to analyse the surface roughness during the AWJ texturing process of stain-less steel 304.